Juvenile Psammomatoid Ossifying Fibroma of Fronto-Ethmoid Complex Mimicking Fibrous Dysplasia: Case Report - Adhikari, Kapil; Pant, Ashok Raj; Koirala, Sapana (Nepalese Journal of Radiology, 2018)
Juvenile Psammomatoid Ossifying Fibromais a rare fibro-osseous tumor seen in children and adolescentand mostly arising from the cranio-facial bone.We report a case of 18-year-old boy who presented with diplopiaand progressive right fronto-orbital swelling. On plain radiograph and CT, it was diagnosed as fibrous dysplasiaand mucocele as differential diagnosis. The tumor was resected and histopathological examination showed psammomatoid features. Therefore, the diagnosis of Juvenile Psammomatoid Ossifying Fibroma must be based on both radiological and histopathological findings.